Optical characteristics of Ge-doped and Er-doped fiber under Proton irradiation - Abdul Halim, Muhammad Danyal Syafiq; Razmi, Nurin Irdina; Baba, Tamana; Saidin, Norazlina; Hasbullah, Nurul Fadzlin; Ahmad, Ishaq (IEEE, 2025)
Satellite and deep-space probe communications rely heavily on optical fibers, yet their performance is significantly affected by proton radiation, which induces material degradation, signal attenuation, and increased noise. This study evaluates the optical degradation of germanium doped and erbium-doped optical fibers under proton radiation, focusing on their suitability for radiation-prone environments. Pre- and post-radiation characterizations were conducted using amplified spontaneous emission (ASE) and optical spectrum analyzers (OSA) to measure radiation-induced attenuation (RIA) within the 1500–1600 nm range. Samples of 5 cm germanium-doped and erbium-doped fibers were irradiated at the National Center for Physics, Islamabad, with energies ranging from 1 MeV to 7 MeV. Results reveal that germanium doped fibers exhibit substantial degradation, with RIA peaking at 12 dB, indicating high sensitivity to radiation, making them suitable for sensor applications. Conversely, erbium-doped fibers show minimal degradation, with a maximum RIA of ~1.5 dB, demonstrating exceptional resilience and suitability for space and extreme environments such as nuclear facilities. These findings highlight the potential of erbium-doped fibers for long-term use in proton radiation environment, while germanium-doped fibers may be more suited for radiation sensitive detection for sensor applications.